General Mathematical Model of the Intersecting Cross-axis Gear based on Conjugate Curve - Shuhong Liu; Rulong Tan; Xiaodong Guo (Jixie chuandong)
In order to solve the problem that it is difficult to complete the full period contact characteristic control of the intersecting cross-axis gear based on the traditional conjugate surfaces meshing theory， a design and analysis method of the intersecting cross-axis gear based on conjugate curves is proposed. In this method， differential geometry and gear kinematics and the conjugate curves meshing theory are applied to deduce the general mathematical model of the conjugate curves intersecting cross-axis gear. The tooth surface curvature analysis and meshing analysis of gear model is carried out and an example is given. The research results have certain guiding significance for the design and manufacture of overload and high-efficiency intersecting cross-axis gear.